ANALYSIS OF TOURIST ATTRACTION ON TOURIST VISITING INTEREST IN PERLANG TOURISM VILLAGE CENTRAL BANGKA - Janice Fellicia Japri; Dewanta Facrureza (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research is motivated by the growing development of Indonesian tourism, one of which is a tourist village. Tourism villages are cultural diversity to tourist destinations owned by each region. The existence of interesting things contained in the tourist village makes tourists interested in visiting Perlang Tourism Village. In this study, it was found that Perlang Tourism Village was included in the top 50 best tourism villages nominated by ADWI and third place in the digital and creative categories. Therefore, the purpose of this study is to provide input to managers on what attractiveness can be developed to become an advantage for Perlang Tourism Village. This research is entitled "Analysis of Tourism Attractiveness of Tourist Visiting Interest in Perlang Village, Central Bangka". This study used a causal analysis method with a quantitative approach. Data collection techniques through observation, interviews, and questionnaires, with 100 research samples selected using non-probability methods and purposive sampling techniques. Data analysis was performed using simple linear regression test, descriptive (mean) test, t test, F test, and R2 analysis. The results of the t test showed that partially the Attraction & Ancillary dimension had a significant influence on visiting interest, while the Amenities &; Accessibility dimension did not have a significant influence. Test F shows that simultaneously, all four dimensions of tourist attraction affect visiting interest. In conclusion, attractiveness has a positive and significant influence on partial interest in visiting. Therefore, this destination must maintain the attractiveness it already has.